Bibliometric and visual analysis in the field of the ketogenic diet in relation to brain health from 2013 to 2024 - Yan, Yuanyuan; Lian, Yuanchu; Li, Zonghuai; Zhang, Bo; Liu, Pingping; Huang, Guihong (Frontiers in Nutrition, 2025)
ObjectivesThe metabolites of the ketogenic diet (KD), specifically ketone bodies (KB), are closely linked to brain health. The KD is widely used to treat epilepsy. It’s also getting more attention for treating neurodegenerative disorders like Alzheimer’s and Parkinson’s diseases, and its effectiveness in these areas is well - recognized. This study aims to explore the research hotspots in the field of KD and brain health from 2013 to 2024, providing references and directions for future research.MethodsThis study utilized R software, VOSviewer, and CiteSpace to analyze 1,162 publications in this field from 2013 to 2024.ResultsA total of 1,162 publications were included in this study. From 2013 to 2021, there was an upward trend in the number of publications in this field, followed by a slight decline from 2021 to 2023. The United States has the highest number of publications and exhibits the most extensive collaboration with other countries, positioning it as the leading nation in this field. The journal Nutrients has the highest number of publications, while Epilepsia is the most cited journal. Key subject terms include KD, Brain, Beta-Hydroxybutyrate, KB, Metabolism, and Oxidative Stress. The primary research focuses in this field are the application of the KD and its metabolites in treating brain disorders such as epilepsy, the role and mechanisms of the KD and its metabolites in brain metabolism, and the effects of the physiological properties of KD metabolites (e.g., KB) such as antioxidative stress and neuroprotection on brain health.ConclusionThe KD is beneficial for brain health, and its use in treating brain disorders has garnered widespread attention and recognition globally. This study provides a comprehensive and in-depth analysis of the literature in this field, offering valuable insights into the research hotspots and future directions for investigation.